Fatigue performance of geosynthetic-reinforced asphalt layers. Issue 6 (24th December 2021) - Kumar, V. V.; Saride, S.; Zornberg, J. G.
Abstract : This study aims at understanding the influence of different geosynthetic reinforcements on the fatigue performance of asphalt layers and the corresponding mechanisms involved. Three different types of geosynthetic reinforcement, namely a biaxial polypropylene geogrid (PP), a polyester geogrid coated with a polymer-modified binder (PET) and a glass geogrid composite (GGC), were employed to understand the fatigue behaviour of asphalt layers via an asphalt beam fatigue test (ABFT) along with the use of digital image correlation (DIC) techniques. The ABFT results suggest that incorporating geosynthetic reinforcement in the asphalt layers improved the fatigue performance by factors of 11, 27, and 38 for the PP, PET, and GGC specimens, respectively. With the aid of DIC, the mechanisms involved in enhancing the fatigue performance of asphalt layers were effectively evaluated. At failure, a maximum tensile strain of 11.2% was obtained using DIC in control specimens against maximum strain values ranging from 2.7 to 3.8% in geosynthetic-reinforced asphalt specimens. Reductions in layer thickness for the geosynthetic-reinforced asphalt layers on the order of 5.9% (PP), 17.6% (PET), and 23.5% (GGC) were established for the geosynthetics evaluated in this study, based on test results adopted in a design example.